Implementation of Linear Congruent Method For Guess the Drawing Game - Sinaga, Magdalena Sinaga; Agustina Simangunsong (SEAN Institute, 2021)
In face guessing game is a game with pictures that will be scrambled and questions in this guess the face game application. Linear Congruent methods are used to generate random values used to randomize images and questions displayed on the guess the face game. Random value generation will be used in this game using lcm formula Xn = ( a (Xn-1) + b mod m. The constantly changing variable value in the game has a significant effect on the random value displayed. The ever-changing administration of a, Xn and b can avoid fixed or repetitive patterns of consecutive random value generation effects. In addition, the provision of variable changes can also prevent the repetition of questions that will be randomized in a row. While to avoid the exit of unwanted random values and used variable m as a limiter maximum value. The implementation of the above method can be concluded that the game guess the face of badminton athletes displays varied images and questions that users can play with their respective difficulty levels.